Effects of Neoadjuvant Denosumab on Radiological and Histological Responses in Patients Undergoing En Bloc Resection for Giant Cell Tumor of Bone: A Systematic Review - Aditama, Hendra; Pratama, Yo Tendy; S, Dhanan Prastanika; K, Dita Anggara; S, Rhyan Dharma (Universitas Airlangga, 2024)
Background: Giant cell tumor of bone (GCTB) is a rare primary bone tumor. The standard treatment is en bloc resection, which can be challenging due to tumor size or location. Denosumab, a monoclonal antibody, has emerged as a promising neoadjuvant therapy for GCTB, potentially facilitating surgical resection. However, its optimal use remains unclear, with debate surrounding its impact on local recurrence. This systematic review aims to synthesize evidence on the histological and radiological changes induced by neoadjuvant denosumab and its impact on surgical outcomes. Methods: This review followed PRISMA guidelines. The medical term